Protocolo de seguridad para contenidos de aprendizaje interactivo de realidad aumentada (2020)
With the incorporation of new technologies in the field ofeducation and virtual learning, it has exponentially increasedthe development of interactive applications and augmentedreality content focused on learning, but in turn, the risksgrow If these systems are violated by cybercriminals with thepurpose of exposing and taking advantage of the privateinformation of the universities, companies and end users forcriminal purposes resulting from economic losses to legalproblems in the Organizations.  In this research, it seeks to address the issue of computersecurity in the development of augmented reality content,through Web server security, risk analysis, types ofvulnerabilities, security policies, methodologies of Softwaredevelopment and testing, among others. Thus posing thenecessary base.  s in the authors responsible for this work tobe able to enter to analyze these contents and to answer toquestions like how safe are these applications? How arethese contents built to be safe and of high quality? What arethe risks for devices or computers hosting these applicationsand augmented reality content? How to mitigate or to solvethe possible risks and failures that these contents cangenerate?  Finally, it is expected to have a test protocol based on theresults were obtained with each of the applications tested,which errors or flaws could have been found, which were thetechniques used to solve these flaws and whatRecommendations should be followed when you startcreating a content of this class